Peningkatan Hasil Belajar Pai Mengunakan Metode Diskusi di Kelas IV SDN 20 Kampung Padang - Yulia, Witry (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education by using the discussion method in grade IV of SD Negeri 20 Kampung Padang. The study was conducted in two cycles, with the first cycle showing that student learning outcomes did not meet the Minimum Completeness Criteria (KKM). In the second cycle, after improvements and clearer explanations of the discussion method, all students successfully met the KKM. The discussion method proved effective in increasing student engagement in learning, enhancing their understanding of the material, and significantly improving learning outcomes. This study concludes that the application of the discussion method can effectively enhance student learning outcomes in Islamic Religious Education.